The p21‐activated kinase 1 (Pak1) signalling pathway in cardiac disease: from mechanistic study to therapeutic exploration - Wang, Yanwen (Br J Pharmacol, 2017)
p21‐activated kinase 1 (Pak1) is a member of the highly conserved family of serine/threonine protein kinases regulated by Ras‐related small G‐proteins, Cdc42/Rac1. It has been previously demonstrated to be involved in cardiac protection. Based on recent studies, this review provides an overview of the role of Pak1 in cardiac diseases including disrupted Ca(2+) homoeostasis‐related cardiac arrhythmias, adrenergic stress‐ and pressure overload‐induced hypertrophy, and ischaemia/reperfusion injury. These findings demonstrate the important role of Pak1 mediated through the phosphorylation and transcriptional modification of hypertrophy and/or arrhythmia‐related genes. This review also discusses the anti‐arrhythmic and anti‐hypertrophic, protective function of Pak1 and the beneficial effects of fingolimod (an FDA‐approved sphingolipid drug), a Pak1 activator, and its ability to prevent arrhythmias and cardiac hypertrophy. These findings also highlight the therapeutic potential of Pak1 signalling in the treatment and prevention of cardiac diseases. LINKED ARTICLES: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc